Health promotion in medium-sized and large companies in Poland in 2017 - activities, implementation, effects and difficulties - Krzysztof Puchalski; Elżbieta Korzeniowska (Nofer Institute of Occupational Medicine, 2019)
Background The paper presents the state of workplace health promotion in Poland as of December 2017. Material and Methods Standardized computer-assisted personal interviews (CAPI) were conducted on a representative sample of 1000 companies employing over 50 people. Results Few companies (37%) actually know the health needs of their employees, whereas 25% admit that they care about health more than it is required by law, and declare their increased involvement in that area. At the same time, 55% of companies sponsor sports tickets, and 52% cover the costs of medical care. Every second company supports physical activity in other ways and improves the working environment. Every third offers medical prophylaxis, takes care of stress reduction and healthy eating habits, or solves the problems of alcohol consumption. The main reasons for such activities are the company's image (79%), good social atmosphere (72%) and employee's work performance (69%), while the prevention of health problems is rarely indicated (43%). The effects of workplace health promotion measures include improved productivity (50%), a better health condition (49%) and an increased identification with the company (47%). As for the obstacles, these is a shortage of financial resources (53%), the lack of favorable fiscal and legal solutions (48%), low interest among employees (45%), the lack of skilled people to manage health promotion (42%) and low awareness of its benefits (37%). Companies that are consciously involved in health promotion and monitor the actual health needs implement more activities, evaluate them more often, recognize their positive effects, and are able to better motivate their employees. Conclusions There is a need to develop systemic solutions that foster health promotion in companies, to disseminate knowledge about the benefits associated with it, and to train the staff responsible for employee health management. Med Pr. 2019;70(3):275-94